2013
DOI: 10.1186/1756-3305-6-111
|View full text |Cite
|
Sign up to set email alerts
|

A multi-locus approach to barcoding in the Anopheles strodei subgroup (Diptera: Culicidae)

Abstract: BackgroundThe ability to successfully identify and incriminate pathogen vectors is fundamental to effective pathogen control and management. This task is confounded by the existence of cryptic species complexes. Molecular markers can offer a highly effective means of species identification in such complexes and are routinely employed in the study of medical entomology. Here we evaluate a multi-locus system for the identification of potential malaria vectors in the Anopheles strodei subgroup.MethodsLarvae, pupa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
80
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(89 citation statements)
references
References 53 publications
4
80
0
5
Order By: Relevance
“…These results show one of the limitations of barcoding identification that is the dependence on available similar sequences for evaluation. Other authors have also reported some difficulties in distinguishing some mosquito close related species by barcoding [44, 45]. Thus, the phylogenetic analysis based on the larger region of cox 1 mtDNA performed in this survey was essential to clarify the identification of Iberian specimens.…”
Section: Discussionmentioning
confidence: 93%
“…These results show one of the limitations of barcoding identification that is the dependence on available similar sequences for evaluation. Other authors have also reported some difficulties in distinguishing some mosquito close related species by barcoding [44, 45]. Thus, the phylogenetic analysis based on the larger region of cox 1 mtDNA performed in this survey was essential to clarify the identification of Iberian specimens.…”
Section: Discussionmentioning
confidence: 93%
“…For example, COI-based barcoding has not been promising in identifying fungi and plant species [27][28][29]. Likewise, COI barcoding has failed to distinguish certain mosquito species of Anopheles and Culex [21][22][23][24][25]. Kumar et al, [23] reported that two closely related mosquito species of the genus Ochlerotatus could not be differentiated using their COI barcode.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have proven that COI gene is an efficient and useful barcode for the identification of metazoans, including mosquitoes [21][22][23][24][25][26]. However, COI barcode may not be universally applicable to identify all animal species.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a multi-locus approach for species identification is necessary (Lahaye et al 2008;Bourke et al 2013;Tripathi et al 2013;Bhagwat et al 2015;Hartvig et al 2015). Though the combinations ITS + matK + psbA-trnH and ITS + rbcL + psbA-trnH were not tested in this study, combined barcodes provide certainly a good species identification for Dalbergia species.…”
Section: Barcodes Performance For Unknown Dalbergia Specimensmentioning
confidence: 99%
“…Standardization, minimization and scalability are three important principles of DNA barcoding (Hollingsworth et al 2011). In several animal DNA barcoding studies the mitochondrial cytochrome oxidase I gene (COI) has shown high ability for species discrimination (Bourke et al 2013;Huang et al 2013). However, this approach is difficult to apply for all plants species because of the low rate of nucleotide substitution in plant mitochondrial genomes (Kress et al 2005).…”
Section: Introductionmentioning
confidence: 99%